Transparent resin composition, dry film, cured product and electronic component

The transparent resin composition with specific polymers and additives addresses the limitations of conventional films by enhancing adhesion and transparency, enabling fine processing and insulation for transparent electronic components.

JP7627320B1Active Publication Date: 2025-02-05TAIYO HOLDINGS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023187236
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-02-05
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

Conventional thermoset-type resin compositions for protective films of transparent electronic components face limitations in miniaturization and achieving high accuracy in opening diameter, with issues in adhesion and transparency when fine-processing is performed.

Method used

A transparent resin composition containing an alkaline-soluble polymer with a cyclohexyl group and carboxyl group, a carboxyl group-containing urethane resin, and a polymerization compound with an ethylene oxide skeleton, along with optional additives like epoxy resin and photopolymerization initiators, is used to form a dried film with improved adhesion and transparency.

Benefits of technology

The composition enables the production of transparent, developable, and adherent films suitable for fine processing, with high transmittance and haze values, suitable for use as insulation protective films for transparent electronic parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627320000001
    Figure 0007627320000001
Patent Text Reader

Abstract

The present invention provides a technology relating to a transparent resin composition having excellent transparency, developability and adhesion. [Solution] One aspect of the present invention is a transparent resin composition. The transparent resin composition contains an alkali-soluble polymer (A), a carboxyl group-containing urethane resin (B), and a polymerizable compound (C). The alkali-soluble polymer (A) contains a cyclohexyl group and a carboxyl group. The carboxyl group-containing urethane resin (B) is obtained by using a compound having an isocyanate group that is not directly bonded to an aromatic ring. The polymerizable compound (C) has an ethylene oxide skeleton. When the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is taken as 100 parts by mass, the content of the alkali-soluble polymer (A) is 45 to 75 parts by mass in terms of solid content.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent resin composition, a dry film, a cured product, and an electronic component. [Background technology]

[0002] There is a demand for transparent insulating protective films as protective films for transparent electronic components such as transparent antennas, transparent displays, etc. Conventionally, thermosetting resin compositions have been known as materials for forming this type of insulating protective film (see Patent Document 1). In addition, transparent electronic components are becoming thinner, lighter, and more flexible, and the use of resin films as transparent organic substrates is being considered. Examples of resin films include polyimide, polyethylene terephthalate, and cycloolefin polymer (COP), and among these, COP, which has excellent optical properties and dimensional stability, is preferably used. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-18893 Summary of the Invention [Problem to be solved by the invention]

[0004] The characteristics required for a protective film for transparent electronic components include transparency, developability, and adhesion to the base (hereinafter simply referred to as adhesion). In recent years, as transparent electronic components have become smaller and thinner, protective films for transparent electronic components are required to have finer opening diameters and higher precision. However, protective films obtained using conventional thermosetting resin compositions have limitations in developability, making it difficult to further finer opening diameters and higher precision. In particular, when microfabrication is performed by a patterning process, physical treatment such as surface roughening is performed on the organic substrate to ensure the transparency of the organic substrate, which makes it impossible to achieve the anchor effect. On the other hand, if the affinity between the organic substrate and the protective film is too high, it becomes difficult to wash away the unexposed areas by development. For this reason, it is necessary to select a protective film that has a suitable adhesion to the organic substrate.

[0005] The present invention has been made in consideration of the above-mentioned problems, and aims to provide a transparent resin composition that is excellent in transparency, developability, and adhesion to organic substrates (particularly adhesion to COP substrates). The present invention also provides a dry film having a resin layer obtained by using the resin composition, a cured product of the transparent resin composition or the resin layer, and an electronic component having the cured product. [Means for solving the problem]

[0006] One embodiment of the present invention is a transparent resin composition, which contains an alkali-soluble polymer (A) containing a cyclohexyl group and a carboxyl group, a carboxyl group-containing urethane resin (B) obtained by using a compound having an isocyanate group not directly bonded to an aromatic ring, and a polymerizable compound (C) having an ethylene oxide skeleton, and the content of the alkali-soluble polymer (A) is 45 to 75 parts by mass in terms of solid content, when the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is taken as 100 parts by mass. In the transparent resin composition of the above embodiment, when the total amount of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is 100 parts by mass, the content of the polymerizable compound (C) may be 20 parts by mass or more in terms of solid content. The transparent resin composition of any of the above embodiments may contain a polymerization initiator. The transparent resin composition of any of the above embodiments may contain an epoxy resin.

[0007] Another aspect of the present invention is a dry film. The dry film is obtained by applying the transparent resin composition of any one of the above aspects onto a first film.

[0008] Yet another aspect of the present invention is a cured product obtained by using the transparent resin composition according to any one of the above aspects or the dry film according to the above aspect. The cured product of the above embodiment may have a transmittance of 85% or more as measured under the following conditions. (conditions) The transparent resin composition is applied onto the first film so that the film thickness after drying is 8 μm, and then heated and dried for 30 minutes in a hot air dryer at 80° C. to form a resin layer. A COP having a film thickness of 50 μm is attached to the exposed surface of the resin layer to perform lamination. After solid exposure using a parallel light exposure machine, the first film is peeled off and development is carried out for 30 seconds using a 1% Na2CO3 aqueous solution at 30°C under conditions of a spray pressure of 0.1 MPa. Thereafter, the coating is thermally cured by heating in a hot air circulation drying oven at 130° C. for 60 minutes to obtain a substrate for transmittance measurement having a cured product with a film thickness of 8 μm. The transmittance of the obtained cured product at 380 to 780 nm is measured using an ultraviolet-visible spectrophotometer. The cured product of any of the above embodiments may be used as an insulating protective film for transparent electronic components. Effect of the Invention

[0009] According to the present invention, a technique can be provided for a transparent resin composition having excellent transparency, developability and adhesion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expression "a to b" in the explanation of a numerical range means that the range is from a to b, unless otherwise specified. In addition, in this specification, the term "(meth)acrylic" includes both "methacrylic" and "acrylic".

[0011] The transparent resin composition according to the embodiment contains an alkali-soluble polymer (A), a carboxyl group-containing urethane resin (B), and a polymerizable compound (C). The transparent resin composition according to the embodiment satisfies a transmittance of 85% or more and a haze of less than 4.0, as measured under atmospheric conditions. The transmittance and haze of the transparent resin composition are measured as follows. First, the transparent resin composition is applied onto a Teflon (registered trademark) panel measuring 75 mm x 14 mm and 40 μm in thickness so that the film thickness after drying is 8 μm, and then heated and dried in a hot air dryer at 80°C for 30 minutes to form a resin layer. Then, cut into pieces measuring 2cm x 4cm and 3cm x 3cm, and peel off the Teflon (registered trademark) to create test pieces. The transmittance is measured by a transmission method using a 2 cm×4 cm test piece and an ultraviolet-visible spectrophotometer (V-570, manufactured by JASCO Corporation) at wavelengths of 380 to 780 nm. The haze is measured using a 3 cm×3 cm test piece with a haze meter (NDH7000II, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0012] (Alkali-soluble polymer (A)) The alkali-soluble polymer (A) contains a cyclohexyl group and a carboxyl group. The alkali-soluble polymer (A) contains a carboxyl group, which can improve adhesion to the base and developability. The alkali-soluble polymer (A) may be a carboxyl group-containing resin having an ethylenically unsaturated group or a carboxyl group-containing resin not having an ethylenically unsaturated group.

[0013] Examples of the alkali-soluble polymer (A) include a copolymer of a monomer containing a cyclohexyl group and a monomer containing a carboxyl group, a modified product in which the terminal portion of a polymer having a cyclohexyl group is substituted with a functional group containing a carboxyl group, a modified product in which the terminal portion of a polymer having a carboxyl group is substituted with a functional group containing a cyclohexyl group, etc. The alkali-soluble polymer (A) is preferably a copolymer of a monomer having a cyclohexyl group and a monomer containing a carboxyl group.

[0014] The monomer having a cyclohexyl group is not particularly limited, and examples thereof include compounds containing a cyclohexyl group and a (meth)acroyl group, such as cyclohexyl (meth)acrylate and 3,4-epoxycyclohexyl (meth)acrylate.

[0015] The monomer containing a carboxyl group is not particularly limited, and examples thereof include compounds containing a carboxyl group and a (meth)acroyl group, such as (meth)acrylic acid and carboxyethyl (meth)acrylate.

[0016] By copolymerizing these monomers under conventionally known conditions, an alkali-soluble polymer (A) can be produced. The ratio of the monomer having a cyclohexyl group to the monomer having a carboxyl group can be any ratio, but a ratio of 30:70 to 70:30 on a mass basis is preferred in terms of adhesion.

[0017] In this case, the monomer of the alkali-soluble polymer (A) may contain a monomer other than the monomer having a cyclohexyl group and the monomer containing a carboxyl group. In other words, the alkali-soluble polymer (A) may be a copolymer of a monomer having a cyclohexyl group, a monomer containing a carboxyl group, and a monomer other than these.

[0018] The alkali-soluble polymer (A) preferably has an ethylenically unsaturated group (a hydrocarbon group having an unsaturated double bond). The ethylenically unsaturated group is preferably a (meth)acryloyl group.

[0019] The alkali-soluble polymer (A) having an ethylenically unsaturated group can be produced, for example, by adding a compound having one epoxy group and one or more ethylenically unsaturated groups (preferably (meth)acryloyl groups) in the molecule, such as glycidyl (meth)acrylate, α-methylglycidyl (meth)acrylate, etc., to a copolymer of a monomer having a cyclohexyl group and a monomer containing a carboxyl group as described above.

[0020] The alkali-soluble polymer (A) can be used alone or in combination of two or more.

[0021] The acid value of the alkali-soluble polymer (A) is preferably 20 to 300 (mgKOH / g), more preferably 40 to 250 (mgKOH / g), and particularly preferably 50 to 200 (mgKOH / g). When the acid value of the alkali-soluble polymer (A) is within this range, it becomes easy to develop the coating film or resin layer after exposure with an aqueous alkali solution, and it becomes easy to draw a more normal cured product pattern.

[0022] The carboxylic acid equivalent of the alkali-soluble polymer (A) is preferably 100 to 1000 (g / eq), more preferably 200 to 800 (g / eq), and particularly preferably 300 to 600 (g / eq). By setting the carboxylic acid equivalent of the alkali-soluble polymer (A) within such range, it becomes easier to obtain a cured product with excellent adhesion and environmental resistance.

[0023] The cyclohexyl group equivalent of the alkali-soluble polymer (A) is preferably 100 to 1000 (g / eq), more preferably 200 to 800 (g / eq), and particularly preferably 300 to 600 (g / eq). By setting the cyclohexyl group equivalent of the alkali-soluble polymer (A) within such range, it becomes easier to obtain a cured product with excellent adhesion and environmental resistance.

[0024] When the alkali-soluble polymer (A) contains a (meth)acryloyl group, the (meth)acrylic equivalent of the alkali-soluble polymer (A) is preferably 100 to 2000 (g / eq), more preferably 200 to 1800 (g / eq), and particularly preferably 300 to 1500 (g / eq). By setting the carboxylic acid equivalent of the alkali-soluble polymer (A) within such a range, it becomes easier to obtain a cured product having excellent resolution, adhesion, and environmental resistance.

[0025] The weight average molecular weight of the alkali-soluble polymer (A) varies depending on the resin skeleton, but can be 1,500 to 150,000, preferably 1,500 to 100,000, more preferably 1,500 to 50,000, and particularly preferably 1,500 to 40,000. When the weight average molecular weight of the alkali-soluble polymer (A) is within this range, a transparent resin composition and a dry film can be obtained that are excellent in tack-free performance, storage stability, moisture resistance of the coating film or resin layer after exposure, and developability, and that can suppress film loss during development and a decrease in resolution.

[0026] The alkali-soluble polymer (A) can be used alone or in combination of two or more.

[0027] (Carboxyl group-containing urethane resin (B)) The carboxyl group-containing urethane resin (B) is obtained by using a compound having an isocyanate group that is not directly bonded to an aromatic ring. The transparent resin composition of the present embodiment contains the carboxyl group-containing urethane resin (B), thereby improving adhesion to the base and developability. The carboxyl group-containing urethane resin (B) may be a carboxyl group-containing urethane resin having an ethylenically unsaturated group, or a carboxyl group-containing urethane resin having no ethylenically unsaturated group. Among them, the carboxyl group-containing urethane resin having an ethylenically unsaturated group is preferable because it has excellent photocurability and development resistance. In addition, the carboxyl group-containing urethane resin (B) preferably has a cyclohexyl group. This can further improve adhesion to the base.

[0028] Specifically, the carboxyl group-containing urethane resin (B) is preferably a urethane resin having a phenolic hydroxyl group introduced at the end by the reaction of a compound (a) having an isocyanate group not directly bonded to an aromatic ring, a compound (b) having two or more alcoholic hydroxyl groups in one molecule, and a compound (c) having one alcoholic hydroxyl group and one or more phenolic hydroxyl groups in one molecule, which also functions as a reaction terminator. In addition, the urethane resin may include a urethane resin obtained by the reaction of a compound (a) having an isocyanate group not directly bonded to an aromatic ring with a compound (b) having two or more alcoholic hydroxyl groups in one molecule, in which a phenolic hydroxyl group is introduced at the molecular side chain using a compound having a phenolic hydroxyl group and two or more alcoholic hydroxyl groups as the compound (b), or a urethane resin in which a carboxyl group is introduced at the molecular side chain using a compound having a carboxyl group and two or more alcoholic hydroxyl groups in one molecule. In the latter urethane resin, the above-mentioned compound (c) having one alcoholic hydroxyl group and one or more phenolic hydroxyl groups in one molecule can be used as an end-capping agent (reaction terminator). In addition, various conventionally known reaction terminators can be used, such as monohydroxyl compounds such as aliphatic alcohols and monohydroxymono(meth)acrylate compounds, and monocarboxylic acids having functional groups capable of undergoing addition reactions or condensation reactions with isocyanate groups, such as alcoholic hydroxyl groups, amino groups, and thiol groups.

[0029] For example, in the case of the preferred urethane resin, the carboxyl group-containing urethane resin (B) may be prepared by mixing and reacting a compound (a) having an isocyanate group not directly bonded to an aromatic ring, a compound (b) having two or more alcoholic hydroxyl groups in one molecule, and a compound (c) having one alcoholic hydroxyl group in one molecule all at once; alternatively, the compound (a) having an isocyanate group not directly bonded to an aromatic ring may be reacted with a compound (b) having two or more alcoholic hydroxyl groups in one molecule, followed by reaction with the compound (c) having one alcoholic hydroxyl group in one molecule, which also functions as a reaction terminator. In the case of the other urethane resins described above, the compound (a) having an isocyanate group not directly bonded to an aromatic ring, the compound (b) having a phenolic hydroxyl group and / or a carboxyl group and two or more alcoholic hydroxyl groups in one molecule, and a reaction terminator may be mixed together and reacted at once, but from the viewpoint of molecular weight adjustment, the compound (a) having an isocyanate group not directly bonded to an aromatic ring may be reacted with the compound (b), and then the reaction terminator may be reacted.

[0030] The reaction proceeds without a catalyst by stirring and mixing at room temperature to 100° C., but in order to increase the reaction rate, it is preferable to heat to 70 to 100° C. The reaction ratio (molar ratio) of the above components (a) to (c) is preferably (a):(b)=1:1 to 2:1, more preferably 1:1 to 1.5:1, and (a+b):(c)=1:0.01 to 0.5, more preferably 1:0.02 to 0.3.

[0031] As the compound (a) having an isocyanate group not directly bonded to an aromatic ring, various known compounds having an isocyanate group not directly bonded to an aromatic ring can be used, and are not limited to a specific compound. Specific examples of the compound (a) having an isocyanate group not directly bonded to an aromatic ring include aliphatic diisocyanates such as hexamethylene diisocyanate, branched aliphatic diisocyanates such as trimethylhexamethylene diisocyanate, isophorone diisocyanate, (o, m, or p)-(hydrogenated) xylene diisocyanate, methylene bis(cyclohexyl isocyanate), cyclohexane-1,3-dimethylene diisocyanate, and cyclohexane-1,4-dimethylene diisocyanate. Among these, hexamethylene diisocyanate, which is an aliphatic diisocyanate, and trimethylhexamethylene diisocyanate, which is a branched aliphatic diisocyanate, are preferred. These compounds having an isocyanate group not directly bonded to an aromatic ring can be used alone or in combination of two or more. When these diisocyanate compounds are used, a cured product having excellent low coloring, environmental resistance, and low warpage can be obtained. In addition, aromatic diisocyanates can also be used within a range that does not impair the effects of the present invention.

[0032] Next, as the compound (b) having two or more alcoholic hydroxyl groups, various polyols known in the art can be used, and are not limited to a specific compound. However, preferred examples of the compound that can be used include polycarbonate polyols such as polycarbonate diol, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, hydrogenated polybutadiene polyols, hydrogenated isoprene polyols, phosphorus-containing diols, bisphenol A alkylene oxide adduct diols, compounds having a carboxyl group and an alcoholic hydroxyl group, compounds having a phenolic hydroxyl group and an alcoholic hydroxyl group, and phosphorus-containing polyols. Examples of the polycarbonate diol include polycarbonate diol (b-1) containing repeating units derived from one or more linear aliphatic diols as constituent units, polycarbonate diol (b-2) containing repeating units derived from one or more alicyclic diols as constituent units, and polycarbonate diol (b-3) containing repeating units derived from both linear aliphatic diols and alicyclic diols as constituent units. In addition, when a compound (b-4) having a carboxyl group and two or more alcoholic hydroxyl groups, or a compound (b-5) having a phenolic hydroxyl group and two or more alcoholic hydroxyl groups, is used, a functional group (phenolic hydroxyl group or carboxyl group) can be provided on the molecular side chain. When a phosphorus-containing polyol (b-6) is used, flame retardancy can be imparted to the urethane resin. These compounds (b-1) to (b-6) can be used alone or in a mixture of two or more.

[0033] Specific examples of the polycarbonate diol (b-1) containing, as a constituent unit, a repeating unit derived from one or more of the above-mentioned linear aliphatic diols include polycarbonate diols derived from 1,6-hexanediol, polycarbonate diols derived from 1,5-pentanediol and 1,6-hexanediol, polycarbonate diols derived from 1,4-butanediol and 1,6-hexanediol, polycarbonate diols derived from 3-methyl-1,5-pentanediol and 1,6-hexanediol, and polycarbonate diols derived from 1,9-nonanediol and 2-methyl-1,8-octanediol.

[0034] A specific example of the polycarbonate diol (b-2) containing, as a constituent unit, a repeating unit derived from one or more of the above-mentioned alicyclic diols is a polycarbonate diol derived from 1,4-cyclohexanedimethanol.

[0035] A specific example of the polycarbonate diol (b-3) containing repeating units derived from both the linear aliphatic diol and the alicyclic diol as constituent units is a polycarbonate diol derived from 1,6-hexanediol and 1,4-cyclohexanedimethanol.

[0036] Specific examples of the compound (b-4) having a carboxyl group and two or more alcoholic hydroxyl groups include dimethylolpropionic acid, dimethylolbutanoic acid, etc. By using these compounds having a carboxyl group and two or more alcoholic hydroxyl groups, the carboxyl group can be easily introduced into the urethane resin.

[0037] Specific examples of the compound (b-5) having the above-mentioned phenolic hydroxyl group and two or more alcoholic hydroxyl groups include 6-hydroxy-5-methyl-1,3-benzenedimethanol, 2,4-di(hydroxymethyl)-6-cyclohexylphenol, 3,3'-methylenebis(2-hydroxy-5-methyl-benzenemethanol), 4,4'-(1-methylethylidene)bis[2-methyl-6-hydroxymethylphenol], 4,4'-[1,4-phenylenebis(1-methylethylidene)bis[2-methyl-6-hydroxymethylphenol], 1,3-benzenedimethanol, 4,4'-methylenebis(2-methyl-6-hydroxymethylphenol), 4,4'-methylenebis(2,5-dimethyl-3-hydroxymethylphenol), 4,4'-cyclohexylidenebis(2-methyl-6-hydroxymethylphenol), 4,4'-cyclohexylidenebis(2-cyclohexyl-6-hydroxymethylphenol), 2,6-bis[(2-hydroxy-3-hydroxymethyl-5-methylphenyl)methyl]-4-methylphenol, 2-hydroxy -5-ethyl-1,3-benzenedimethanol, 2-hydroxy-4,5-dimethyl-1,3-benzenedimethanol, 2-hydroxy-5-(1-methylpropyl)-1,3-benzenedimethanol, 4-(1,1-dimethylethyl)-2-hydroxy-1,3-benzenedimethanol, 2-hydroxy-5-cyclohexyl-1,3-benzenedimethanol, 2-hydroxy-5-(1,1,3,3-tetramethylbutyl)-1,3-benzenedimethanol, 2,6-bis[(4-hydroxy-3-hydroxymethyl-2,5-dimethylphenyl)methy] [(4-hydroxy-3-hydroxymethyl-2,5-dimethylphenyl)methyl]-4-cyclohexylphenol, 2-hydroxy-1,3,5-benzenetrimethanol, 3,5-dimethyl-2,4,6-trihydroxymethylphenol, 4,4',4"-ethylidinetris(2-methyl-6-hydroxymethylphenol), 2,3,5,6-tetra(hydroxymethyl)-1,4-benzenediol, 4,4'-methylenebis[2,6-bis(hydroxymethyl)phenol], and the like.By using these compounds having a phenolic hydroxyl group and an alcoholic hydroxyl group, the phenolic hydroxyl group can be easily introduced into the urethane resin.

[0038] The polycarbonate diol preferably has a number average molecular weight of 200 to 5,000. When the polycarbonate diol contains repeating units derived from a linear aliphatic diol and an alicyclic diol as constituent units and the copolymerization ratio of the linear aliphatic diol to the alicyclic diol is 3:7 to 7:3 by mass, the polycarbonate diol preferably has a number average molecular weight of 400 to 2,000.

[0039] Examples of the above-mentioned bisphenol A-based alkylene oxide adducts include ethylene oxide adducts, propylene oxide adducts, and butylene oxide adducts of bisphenol A.

[0040] Specific examples of the phosphorus-containing polyol include FC-450 (manufactured by Asahi Denka Kogyo Co., Ltd.), M-Ester (manufactured by Sanko Co., Ltd.), and M-Ester-HP (manufactured by Sanko Co., Ltd.) etc. By using this phosphorus-containing polyol, a phosphorus compound can be introduced into the urethane resin.

[0041] Next, as the compound (c) having one alcoholic hydroxyl group, various monohydroxy compounds known in the art can be used, and are not limited to specific compounds. Examples of the compound include, but are not limited to, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, t-butanol, amyl alcohol, hexyl alcohol, octyl alcohol, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, cyclohexane dimethanol mono(meth)acrylate, caprolactone or alkylene oxide adducts of the above (meth)acrylates, glycerin di(meth)acrylate, trimethylol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, allyl alcohol, allyloxyethanol, glycolic acid, and hydroxypivalic acid.

[0042] The compound (c) having a phenolic hydroxyl group and one alcoholic hydroxyl group per molecule is used for the purpose of introducing a phenolic hydroxyl group into polyurethane, and also functions as a terminal blocking agent for polyurethane. In particular, a compound having one alcoholic hydroxyl group and a phenolic hydroxyl group per molecule that can react with isocyanate functions as a reaction terminator. Specific examples of such a compound (c) include, for example, hydroxymethylphenol, hydroxymethylcresol, hydroxymethyl-di-t-butylphenol, p-hydroxyphenyl-2-methanol, p-hydroxyphenyl-3-propanol, p-hydroxyphenyl-4-butanol, hydroxyethylcresol, 2,6-dimethyl-4-hydroxymethylphenol, 2,4-dimethyl-6-hydroxymethylphenol, 2,3,6-trimethyl-4-hydroxymethylphenol, 2-cyclohexyl-4-hydroxymethyl-5-methylphenol, 4-methyl-6-hydroxymethylbenzene-1,2-diol, 4-(1,1-dimethylphenyl)-2- ...2-methyl-4-hydroxymethylphenol, 2-cyclohexyl-4-hydroxymethyl-2-methyl-4-hydroxymethylphenol, 2-cyclohexyl-4-hydroxymethyl-2-methyl-4-hydroxymethylphenol, 2-cyclohex Examples of the compound (c) include, but are not limited to, hydroxyalkylphenols or hydroxyalkylcresols such as (ethylethyl)-6-hydroxymethylbenzene-1,2-diol, esters of phenols having a carboxyl group-containing substituent such as hydroxybenzoic acid, hydroxyphenylbenzoic acid, or hydroxyphenoxybenzoic acid with ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, and the like, monoethylene oxide adducts of bisphenols, monopropylene oxide adducts of bisphenols, p-hydroxyphenethyl alcohol, and the like. These compounds (c) can be used alone or in combination of two or more.

[0043] The weight average molecular weight of the carboxyl group-containing urethane resin (A) is preferably 500 to 100,000, more preferably 8,000 to 50,000. Here, the weight average molecular weight is a value measured by gel permeation chromatography in terms of polystyrene. When the weight average molecular weight of the carboxyl group-containing urethane resin (A) is 500 or more, the elongation, flexibility, and strength of the cured film are improved, and when it is less than 100,000, the resin is developable, has improved solubility, and does not become too high in viscosity after dissolution.

[0044] The acid value of the carboxyl group-containing urethane resin (B) is preferably in the range of 10 to 120 mgKOH / g, more preferably 20 to 80 mgKOH / g. When the acid value is 10 mgKOH / g or more, the reactivity with the thermosetting component is improved, and the heat resistance is improved. On the other hand, when the acid value is 120 mgKOH / g or less, the resist properties such as the alkali resistance and electrical properties of the cured film are improved. The acid value of the resin is a value measured in accordance with JIS K5601-1-2-1:1999.

[0045] These carboxyl group-containing urethane resins (B) may be used alone or in combination of two or more.

[0046] When the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is taken as 100 parts by mass, the content of the alkali-soluble polymer (A) is 45 to 75 parts by mass, preferably 50 to 70 parts by mass, and the content of the carboxyl group-containing urethane resin (B) is 25 to 55 parts by mass, preferably 30 to 50 parts by mass, calculated as solid content. By setting the blending ratio (content ratio) of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) within the above range, it is possible to further increase the developability and transparency, and also improve the adhesion to the base.

[0047] (Polymerizable compound (C)) The polymerizable compound (C) has an ethylene oxide skeleton and is represented, for example, by the following formula (1). R1-(CCO)n-R2 (1) In formula (1), R1 and R2 are each independently a monovalent organic group having an unsaturated double bond, such as a (meth)acrylate group or a vinyl group. n represents the number of repetitions of the ethylene oxide group and is an integer of 1 or more. n is preferably 2 to 30.

[0048] Specific examples of the polymerizable compound (C) include ethoxylated bisphenol A dimethacrylate, polyether-modified (EO-modified) acrylate oligomer, and ethoxylated glycerin triacrylate.

[0049] When the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is taken as 100 parts by mass, the content of the polymerizable compound (C) is preferably 15 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 30 parts by mass or more, and particularly preferably 35 parts by mass or more. The upper limit of the content of the polymerizable compound (C) is not particularly limited as long as it does not impair the effects of the present invention, and is, for example, 60 parts by mass or less, 55 parts by mass or less, 50 parts by mass or less, or 45 parts by mass or less when the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is taken as 100 parts by mass.

[0050] (Other ingredients) The transparent resin composition of the present embodiment may contain a polymerization initiator. The polymerization initiator may be either a thermal polymerization initiator or a photopolymerization initiator, but is preferably a photopolymerization initiator. Examples of the photopolymerization initiator include benzoin and benzoin alkyl ethers such as benzoin, benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, and 1,1-dichloroacetophenone; 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylphenylacetophenone, and the like; Aminoalkylphenones such as 1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, and 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone; anthraquinones such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-tertiary butylanthraquinone, and 1-chloroanthraquinone; 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2-chloroanthraquinone; Thioxanthones such as thioxanthone and 2,4-diisopropylthioxanthone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenones such as 4,4'-bis(diethylamino)benzophenone; (2,6-dimethoxybenzoyl)-2,4,4-pentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, ethyl-2,4,6-trimethylbenzoylphenylphosphine oxide phosphine oxides such as finate; oxime esters such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime), 9-ethyl-6-nitro-9H-carbazol-3-yl)(4-((1-methoxypropan-2-yl)oxy)-2-methylphenyl)methanone O-acetyloxime; various peroxides, titanocene initiators, and the like.These may be used in combination with a photosensitizer such as tertiary amines such as N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid isoamyl ester, pentyl-4-dimethylaminobenzoate, triethylamine, triethanolamine, etc. These photopolymerization initiators may be used alone or in combination of two or more kinds.

[0051] The blending amount of the photopolymerization initiator other than the oxime esters is preferably 0.01 to 30 parts by mass, more preferably 0.5 to 28 parts by mass, and even more preferably 1.0 to 25 parts by mass, when the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) in the transparent resin composition of this embodiment is 100 parts by mass. The blending amount of the photopolymerization initiator of the oxime esters is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 7.0 parts by mass, and even more preferably 0.01 to 5.0 parts by mass, when the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) in the transparent resin composition of this embodiment is 100 parts by mass.

[0052] The transparent resin composition of the present embodiment may contain an epoxy resin as a thermosetting component. Examples of the epoxy resin include bifunctional epoxy resins such as bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, brominated bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bixylenol type epoxy resins, biphenyl type epoxy resins, biphenol type epoxy resins, and trisphenol type epoxy resins. Examples of the polyfunctional epoxy resins include novolac type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, N-glycidyl type epoxy resins, bisphenol A novolac type epoxy resins, bixylenol type epoxy resins, biphenol novolac type epoxy resins, chelate type epoxy resins, glyoxal type epoxy resins, amino group-containing epoxy resins, rubber-modified epoxy resins, dicyclopentadiene phenolic type epoxy resins, diglycidyl phthalate resins, heterocyclic epoxy resins, tetraglycidyl xylenoyl ethane resins, silicone-modified epoxy resins, and ε-caprolactone-modified epoxy resins. Further preferred examples of epoxy resins which can easily give a cured product having high transparency include bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, brominated bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bixylenol type epoxy resins, biphenyl type epoxy resins, and biphenol type epoxy resins. Specific examples of such epoxy resins include biphenyl novolac epoxy resin NC-3000 (manufactured by Nippon Kayaku Co., Ltd.), biphenyl type epoxy resin YX-4000 (manufactured by Mitsubishi Chemical Corporation), hydrogenated bisphenol A type epoxy resin YX-8034 (manufactured by Mitsubishi Chemical Corporation), bisphenol A type epoxy resin JER-828 (manufactured by Mitsubishi Chemical Corporation), mixed resin ST6100 of bisphenol A type epoxy and hydrogenated bisphenol A type epoxy (manufactured by Nippon Steel Chemical & Material Co., Ltd.), and trisphenol type epoxy resin VG-3101L (manufactured by Printec Co., Ltd.). The epoxy resin is preferably difunctional or trifunctional, which can further increase the transparency of the cured product obtained from the transparent resin composition. In order to impart flame retardancy, an epoxy resin having an atom of a halogen such as chlorine or bromine or an atom of phosphorus introduced into its structure may be used.

[0053] The amount of the epoxy resin is preferably 5 to 150 parts by mass, more preferably 10 to 80 parts by mass, and even more preferably 20 to 70 parts by mass, when the total amount of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is taken as 100 parts by mass. By making the amount of the epoxy resin 5 parts by mass or more, the strength of the cured film can be increased. On the other hand, by making the amount of the epoxy resin 150 parts by mass or less, the flexibility, transparency, environmental resistance, adhesion and electrical properties can be increased.

[0054] The transparent resin composition of the present embodiment may contain a filler to the extent that the effect is not impaired. The filler can be used to improve the mechanical strength of a cured product of the transparent resin composition or to improve the coatability of the transparent resin composition.

[0055] Examples of the filler include metal oxides such as silica, alumina, and titanium oxide; metal hydroxides such as aluminum hydroxide and magnesium hydroxide; clay minerals such as talc and mica; fillers having a ferrovskite crystal structure such as barium titanate and strontium titanate; inorganic fillers such as boron nitride, aluminum borate, barium sulfate, and calcium carbonate; fluororesin fillers such as polytetrafluoroethylene (PTFE), tetrafluoroethylene / ethylene copolymer (ETFE), tetrafluoroethylene / perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene / hexafluoropropylene copolymer (FEP), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF), and polyvinyl fluoride (PVF); and organic fillers such as hydrocarbon resin fillers such as cycloolefin polymer (COP) and cycloolefin copolymer (COC). One type of filler may be used alone, or two or more types may be used in combination.

[0056] Among the above-mentioned fillers, it is preferable to contain silica from the viewpoint of improving the coatability of the transparent resin composition. From the viewpoint of transparency, the silica used preferably has an average particle size of 1 to 100 nm, and more preferably has an average particle size of 1 to 50 nm. Examples of such silica include AEROSIL 90, AEROSIL 130, AEROSIL 150, AEROSIL 200, AEROSIL 225, AEROSIL 300, AEROSIL 380, AEROSIL OX50, AEROSIL TT600, AEROSIL R104, AEROSIL R106, AEROSIL R202, AEROSIL R711, AEROSIL R805, AEROSIL R812, AEROSIL R816, AEROSIL R972, AEROSIL R974, AEROSIL R7200, AEROSIL R8200, and AEROSIL R9200 (manufactured by Nippon Aerosil Co., Ltd.).

[0057] When the transparent resin composition of the present embodiment contains a filler, the content of the filler is preferably 1 to 20 parts by mass, and more preferably 3 to 20 parts by mass, when the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) in the transparent resin composition is taken as 100 parts by mass. By having the filler content within the above range, it is possible to obtain a transparent resin composition that has excellent coatability while maintaining the transparency of the transparent resin composition and its cured product.

[0058] The transparent resin composition of the present embodiment may contain an organic solvent. The organic solvent can be used to easily dissolve or disperse each component in the transparent resin composition, or to adjust the viscosity to a level suitable for coating.

[0059] Examples of organic solvents include toluene, xylene, ethylbenzene, nitrobenzene, cyclohexane, isophorone, diethylene glycol dimethyl ether, ethylene glycol diethyl ether, carbitol acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, dipropylene glycol methyl ether acetate, diethylene glycol ethyl ether acetate, methyl methoxypropionate, ethyl methoxypropionate, methyl ethoxypropionate, ethyl ethoxypropionate, ethyl acetate, n-butyl acetate, isoamyl acetate, ethyl lactate, acetone, methyl ethyl ketone, cyclohexanone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, γ-butyrolactone, dimethyl sulfoxide, chloroform, and methylene chloride. The amount of organic solvent to be blended can be appropriately set according to the desired viscosity.

[0060] The transparent resin composition of the present embodiment may contain, as other components, various additives such as a defoaming agent, an adhesion imparting agent or a leveling agent, known and commonly used polymerization inhibitors such as hydroquinone, hydroquinone monomethyl ether, pyrogallol, tertiary butyl catechol, and phenothiazine, coupling agents, dispersants, and flame retardants, within a range that does not impair the effects of the present invention.

[0061] (Dry film) The dry film according to the embodiment has a resin layer obtained by applying the transparent resin composition of the above-mentioned form to at least one surface of a first film (base film) and then drying it. When used, this resin layer is laminated so as to be in contact with a base material or a substrate.

[0062] The transparent resin composition of the above-mentioned form is uniformly applied to a first film (substrate film) by an appropriate method such as a blade coater, lip coater, comma coater, or film coater, and then dried to form the above-mentioned resin layer, and preferably a second film (so-called cover film (protective film)) is laminated thereon to produce the dry film according to the embodiment. The second film and the first film may be made of the same film material or different films.

[0063] The film materials used for the first film and the second film can be any of those known to be used for dry films. The first film can be a thermoplastic film such as a polyester film such as polyethylene terephthalate having a thickness of 2 to 150 μm. The second film can be a polyethylene film, a polypropylene film, or the like. However, it is preferable that the film used for the second film has a smaller adhesive strength with the resin layer than the first film.

[0064] The thickness of the resin layer in the dry film according to the embodiment is preferably 200 μm or less, and more preferably in the range of 5 to 50 μm.

[0065] (cured product) The cured product according to the embodiment can be obtained by curing the transparent resin composition or dry film of the above-mentioned aspect in a predetermined step. The patterned cured film, which is the cured product, may be produced by a known and commonly used method, for example, as follows.

[0066] In step 1, a transparent resin composition is applied onto a substrate and dried to obtain a resin layer. When a dry film is used, the resin layer is formed on the substrate by laminating the dry film onto the substrate using a laminator or the like so that the resin layer comes into contact with the substrate. As a method for applying the transparent resin composition onto a substrate, a method that has conventionally been used for applying transparent resin compositions can be used, such as a method of applying using a spin coater, a bar coater, a blade coater, a curtain coater, a screen printing machine, or the like, a method of spray application using a spray coater, and further an inkjet method. In addition, the method of laminating the dry film onto the substrate is preferably carried out under pressure and heat using a vacuum laminator or the like. By using such a vacuum laminator, when a substrate on which a circuit is formed is used, even if the substrate has unevenness on its surface, the dry film adheres closely to the substrate, so that no air bubbles are mixed in, and the filling of recesses on the substrate surface is improved. The pressure condition is preferably about 0.1 to 2.0 MPa, and the heating condition is preferably 40 to 120°C. The drying method performed after applying the transparent resin composition may be air drying, heat drying using an oven or a hot plate, vacuum drying, IR dryer, etc. The drying conditions are not particularly limited, but natural drying, air drying, or heat drying may be performed at 60 to 130° C. for 1 to 30 minutes. There are no particular limitations on the substrate on which the resin layer is formed, and examples include printed wiring boards and flexible printed wiring boards on which circuits have already been formed using copper or the like, as well as materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven cloth epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, copper-clad laminates for high-frequency circuits made from fluororesin, polyethylene, polyphenylene ether, polyphenylene oxide, cyanate, etc., including copper-clad laminates of all grades (FR-4, etc.), as well as metal substrates, polyimide films, cycloolefin polymer films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer plates, etc.

[0067] Next, in step 2, the resin layer is irradiated (exposed) with light through a photomask having a pattern, or directly in a pattern. In the method of laminating a dry film, the first film is peeled off from the dry film after exposure. As long as the characteristics are not impaired, the first film may be peeled off from the dry film before exposure to expose the exposed resin layer. For exposure, any device equipped with a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, or the like and capable of irradiating ultraviolet light in the range of 350 to 450 nm may be used, and further, a direct imaging device (for example, a laser direct imaging device that directly draws an image with a laser based on CAD data from a computer) may also be used. The lamp light source or laser light source of the direct imaging device may have a maximum wavelength in the range of 350 to 450 nm. The amount of exposure varies depending on the film thickness, etc., but is generally 10 to 1000 mJ / cm. 2 , preferably 20 to 900 mJ / cm 2 The range may be:

[0068] Next, in step 3, the resin layer after the exposure is treated with a developer, whereby the unexposed parts of the resin are removed, and a patterned film of the transparent resin composition according to the embodiment can be formed.

[0069] The method used for development can be arbitrarily selected from among a dipping method, a shower method, a spray method, a brush method, and the like. Examples of the developer include aqueous solutions of inorganic alkalis such as sodium hydroxide, sodium carbonate, sodium silicate, and aqueous ammonia, organic amines such as ethylamine, diethylamine, triethylamine, and triethanolamine, and quaternary ammonium salts such as tetramethylammonium hydroxide and tetrabutylammonium hydroxide. If necessary, an appropriate amount of a water-soluble organic solvent or surfactant such as methanol, ethanol, and isopropyl alcohol may be added to the developer. Thereafter, if necessary, the coating film is washed with a rinse liquid to obtain a pattern film. As the rinse liquid, distilled water, methanol, ethanol, isopropyl alcohol, and the like may be used alone or in combination. The above-mentioned solvents may also be used as the developer.

[0070] In addition, as necessary, in step 4, the pattern film may be irradiated with active energy rays and then heat-cured, or may be irradiated with active energy rays after heat-curing, or may be heat-cured only to perform final finish curing (main curing). The heating temperature is not particularly limited, but may be, for example, heating at 100 to 220°C for about 30 to 120 minutes. The atmosphere (gas) used in this step may be air, or an inert gas such as nitrogen or argon.

[0071] The cured product according to the embodiment preferably has a transmittance of 85% or more as measured under the following conditions, which allows the cured product to be suitably used as an insulating protective film for transparent electronic components. (conditions) The transparent resin composition is applied onto the first film so that the film thickness after drying is 8 μm, and then heated and dried for 30 minutes in a hot air dryer at 80° C. to form a resin layer. A COP film having a thickness of 50 μm is attached to the exposed surface of the resin layer so as to be in contact with the film, and lamination is performed. After solid exposure using a parallel light exposure machine, the first film is peeled off and development is carried out for 30 seconds using a 1% Na2CO3 aqueous solution at 30°C under conditions of a spray pressure of 0.1 MPa. Thereafter, the coating is thermally cured by heating in a hot air circulation drying oven at 130° C. for 60 minutes to obtain a substrate for transmittance measurement having a cured product with a film thickness of 8 μm. The transmittance of the obtained cured product at 380 to 780 nm is measured using an ultraviolet-visible spectrophotometer.

[0072] (Electronic Components) The electronic component according to the embodiment has the cured product of the above-mentioned aspect. The cured product is not only excellent in transparency, but also suitable for microfabrication and has good adhesion, so that it is suitable for use as an insulating protective film for transparent electronic components. Examples of transparent electronic components include transparent antennas and transparent displays. More specifically, the cured product of the above-mentioned embodiment is suitably used for surface protective films in transparent electronic components, interlayer insulating films, insulating films for rewiring, protective films for flip-chip devices, protective films for devices having a bump structure, interlayer insulating films in multilayer circuits, insulating materials for passive components, and protective films for printed wiring boards such as solder resists and coverlay films.

[0073] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES

[0074] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.

[0075] The transparent resin compositions of each Example and Comparative Example were prepared by blending the components shown in Table 1, mixing them with a stirrer, and dispersing them with a roll or bead mill. The numerical values ​​in the table indicate the parts by mass of the solid content.

[0076] The details of Synthesis Examples 1 to 3 shown in Table 1 are as follows.

[0077] (Synthesis Example 1: Synthesis of an alkali-soluble polymer having a cyclohexyl group and a carboxy group) In a four-neck flask equipped with a reflux condenser, a thermometer, a glass tube for nitrogen replacement, and a stirrer, 223.8g (2.6mol) of methacrylic acid, 100.1g (1.0mol) of methyl methacrylate, 246.7g (1.6mol) of cyclohexyl acrylate, 1400g of dipropylene glycol methyl ether, and 16.4g (0.1mol) of azobisisobutyronitrile were added, and the mixture was heated at 75°C for 5 hours under a nitrogen stream to allow the polymerization reaction to proceed. After adding 17.0g (0.07mol) of triphenylphosphine, 156.4g (1.1mol) of glycidyl methyl methacrylate was added, and the mixture was heated at 90-100°C for 6 hours to add acrylic groups. Thereafter, triphenylphosphine was deactivated by air bubbling to obtain an alkali-soluble polymer solution having a cyclohexyl group and a carboxyl group (solid acid value: 110 mgKOH / g, solid concentration: 35 mass %, molecular weight Mw: 15000).

[0078] (Synthesis Example 2: Synthesis of urethane resin using a compound having an isocyanate group and a cyclohexyl group that are not directly bonded to an aromatic ring) Into a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 360 g (0.45 mol) of polycarbonate diol (number average molecular weight 800) derived from 1,5-pentanediol and 1,6-hexanediol as a compound having two or more alcoholic hydroxyl groups, 81.4 g (0.55 mol) of dimethylolbutanoic acid, and 22.1 g (0.16 mol) of hydroxyphenylethyl alcohol as a compound having one alcoholic hydroxyl group and one or more phenolic hydroxyl groups in one molecule were charged. Next, 283.0g (1.08mol) of dicyclohexylmethane-4,4-diisocyanate was added as a compound having an isocyanate group not directly bonded to an aromatic ring and a cyclohexyl group, and the mixture was heated to 60°C while stirring and stopped. When the temperature in the reaction vessel began to drop, the mixture was heated again and stirred at 80°C. The reaction was terminated when it was confirmed that the absorption spectrum (2280cm-1) of the isocyanate group had disappeared in the infrared absorption spectrum. Next, carbitol acetate was added so that the solid content was 50wt%, and a urethane resin was obtained using a compound having an isocyanate group and a cyclohexyl group not directly bonded to an aromatic ring. The acid value of the solid content of the obtained urethane resin using a compound having an isocyanate group and a cyclohexyl group not directly bonded to an aromatic ring was 41.3mgKOH / g.

[0079] (Synthesis Example 3: Synthesis of urethane resin using a compound having an isocyanate group not directly bonded to an aromatic ring but not having a cyclohexyl group) Into a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 360 g (0.45 mol) of polycarbonate diol (number average molecular weight 800) derived from 1,5-pentanediol and 1,6-hexanediol as a compound having two or more alcoholic hydroxyl groups, 81.4 g (0.55 mol) of dimethylolbutanoic acid, and 22.1 g (0.16 mol) of hydroxyphenylethyl alcohol as a compound having one alcoholic hydroxyl group and one or more phenolic hydroxyl groups in one molecule were charged. Next, 200.9g (1.08mol) of trimethylhexamethylene diisocyanate was added as a compound having an isocyanate group not directly bonded to an aromatic ring but not having a cyclohexyl group, and the mixture was heated to 60°C while stirring and stopped. When the temperature in the reaction vessel began to drop, the mixture was heated again and continued stirring at 80°C. The reaction was terminated when it was confirmed that the absorption spectrum (2280cm-1) of the isocyanate group had disappeared in the infrared absorption spectrum. Next, carbitol acetate was added so that the solid content was 50wt%, and a urethane resin was obtained using a compound having an isocyanate group not directly bonded to an aromatic ring but not having a cyclohexyl group. The acid value of the solid content of the obtained urethane resin using a compound having an isocyanate group not directly bonded to an aromatic ring but not having a cyclohexyl group was 48.8mgKOH / g.

[0080] (Synthesis Example 4: Synthesis of urethane resin using a compound having an isocyanate group directly bonded to an aromatic ring) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 360 g (0.45 mol) of polycarbonate diol (number average molecular weight 800) derived from 1,5-pentanediol and 1,6-hexanediol as a compound having two or more alcoholic hydroxyl groups, 81.4 g (0.55 mol) of dimethylol butanoic acid, and 11.8 g (0.16 mol) of n-butanol as a molecular weight regulator (reaction terminator) were added. Next, 187.9 g (1.08 mol) of tolylene diisocyanate as a compound having an isocyanate group directly bonded to an aromatic ring was added, and the mixture was heated to 60°C while stirring, and the mixture was stopped. When the temperature in the reaction vessel began to decrease, the mixture was heated again and stirring was continued at 80°C, and the absorption spectrum of the isocyanate group (2280 cm) was measured by infrared absorption spectroscopy. -1 The reaction was terminated when it was confirmed that the carboxyl group had disappeared. Carbitol acetate was then added so that the solid content was 50 wt%, and a viscous liquid carboxyl group-containing urethane resin (varnish D) containing a diluent was obtained. The acid value of the solid content of the obtained carboxyl group-containing urethane resin was 49.5 mg KOH / g.

[0081] <Preparation of dry film for evaluation> The transparent resin composition of each Example and Comparative Example was applied onto a polyethylene film (E5041, manufactured by Toyobo Co., Ltd.) measuring 95 mm×150 mm and having a thickness of 25 μm so that the film thickness after drying was 8 μm, and the composition was dried by heating in a hot air dryer at 80° C. for 30 minutes to form a resin layer, and a biaxially oriented polypropylene film (MA-411, manufactured by Oji F-Tex Co., Ltd.) measuring 95 mm×150 mm and having a thickness of 15 μm was laminated onto the resin layer to obtain a dry film for evaluation. When the transparent resin composition of Example 13 was used, it was confirmed that the coatability onto the polyethylene film was better than that of the other Examples.

[0082] <Developability> The biaxially stretched polypropylene film of each dry film prepared in <Preparation of dry film for evaluation> was peeled off, and the exposed resin layer side was attached so as to come into contact with a COP film (ZEONER ZF14, manufactured by Zeon Corporation (haze value 1.8%)) having a size of 90 mm × 150 mm and a thickness of 50 μm. Using a two-chamber vacuum laminator (manufactured by Nikko Materials Co., Ltd., CVP-300), using only the first chamber, the substrate and dry film were laminated under conditions of temperature 70°C, evacuation time 20 seconds, pressure 0.4 MPa, and pressurization time 40 seconds, and the substrate was allowed to cool to room temperature to prepare a substrate for development evaluation.

[0083] The substrate for evaluating developability prepared by the above-mentioned method was developed by spraying a developer (aqueous solution of 1% by mass Na2CO3 at a liquid temperature of 30°C) at a spray pressure of 0.1 MPa for 30 seconds. The haze value of the COP substrate after development was measured with a haze meter (NDH-7000II manufactured by Nippon Denshoku Industries Co., Ltd.) to confirm the presence or absence of residue. The evaluation results are shown in Table 1. The haze value of the COP substrate alone was 1.8%. A+ (excellent): The haze value of the COP substrate was less than 2.5%. A (good): The haze value of the COP substrate was 2.5% or more and less than 3.0%. B (Acceptable): The haze value of the COP substrate was 3.0% or more and less than 3.5%. C (unacceptable): The haze value of the COP substrate was 3.5% or more.

[0084] <Transmittance measurement> The biaxially stretched polypropylene film of the dry film prepared in <Preparation of dry film for evaluation> was peeled off, and the exposed resin layer side was attached so that it was in contact with a COP film (ZEONER ZF14, Zeon Corporation, transmittance 90% or more) with a size of 95 mm x 150 mm and a thickness of 50 μm. The COP film and the dry film were laminated using a two-chamber vacuum laminator (Nikko Materials Corporation, CVP-300) with only the first chamber under conditions of temperature 70°C, vacuum time 20 seconds, pressure 0.4 MPa, and pressure time 40 seconds, and a parallel light exposure machine (EXP2960, ORC Manufacturing Co., Ltd.) was used to place Kodak step tablet No. 2 on the film and expose it to light at the optimal exposure amount so that the number of steps after development would be 5. After peeling off the polyethylene film, the film was developed for 30 seconds using a 1% Na2CO3 aqueous solution at 30°C at a spray pressure of 0.1 MPa. Thereafter, the coating was thermally cured by heating in a hot air circulation drying oven at 130° C. for 60 minutes to obtain a substrate for transmittance measurement having a fully cured product with a film thickness of 8 μm. The transmittance of the obtained cured product at 380 to 780 nm was measured using an ultraviolet-visible spectrophotometer (V-570, manufactured by JASCO Corporation).

[0085] The obtained transmittance was evaluated according to the following criteria. A+ (excellent): 90% or more A (Good): 85% to less than 90% B (Acceptable): 70% or more but less than 85% C (Fail): Less than 70%

[0086] <Haze measurement> The biaxially stretched polypropylene film of the dry film prepared in <Preparation of dry film for evaluation> was peeled off, and the exposed resin layer side was attached so that it was in contact with a COP film (ZEONER ZF14, Zeon Corporation) with a size of 95 mm × 150 mm and a thickness of 50 μm. Using a two-chamber vacuum laminator (Nikko Materials Co., Ltd., CVP-300), the COP film and the dry film were laminated using only the first chamber under conditions of temperature 70 °C, vacuum time 20 seconds, pressure 0.4 MPa, and pressure time 40 seconds, and a parallel light exposure machine (EXP2960, ORC Manufacturing Co., Ltd.) was used to place Kodak step tablet No. 2 on the film and expose it to light at the optimal exposure amount so that the number of steps after development would be 5. After peeling off the polyethylene film, the film was developed for 30 seconds using a 1% Na2CO3 aqueous solution at 30 °C at a spray pressure of 0.1 MPa. Thereafter, the coating was thermally cured by heating in a hot air circulation drying oven at 130° C. for 60 minutes to obtain a substrate for haze measurement having a fully cured product with a film thickness of 8 μm. The haze value of the substrate for haze measurement was measured using a haze meter (NDH7000II, manufactured by Nippon Denshoku Industries Co., Ltd.). The haze values ​​obtained were evaluated according to the following criteria. The results are shown in Table 1. A+ (Excellent): Less than 4.0% A (Good): 4.0% or more and less than 4.5% B (Acceptable): 4.5% or more and less than 7.0% C (impossible): 7.0% or more

[0087] <Transmittance measurement after constant temperature and humidity test> The COP film having a thickness of 8 μm and a fully cured product formed thereon, which was used for the transmittance measurement, was allowed to stand for 500 hours under conditions of 85° C. and 85 RH%, and then the transmittance was measured and evaluated as described above.

[0088] <Haze after constant temperature and humidity test> The COP film having a thickness of 8 μm and a fully cured product formed thereon, which was used for the haze measurement, was allowed to stand for 500 hours under conditions of 85° C. and 85 RH%, and then the above-mentioned haze measurement and evaluation were carried out.

[0089] <COP Adhesion> The biaxially stretched polypropylene film of the dry film produced in <Production of Dry Film for Evaluation> was peeled off, and the exposed resin layer side was laminated onto a COP film (ZEONEX ZF14, manufactured by Nippon Zeon Co., Ltd.) with a size of 95 mm × 150 mm and a thickness of 50 μm so that they were in contact. Using a 2-chamber type vacuum laminator (CVP-300, manufactured by Niko Materials Co., Ltd.), the COP film and the dry film were laminated using only the first chamber under the conditions of a temperature of 70°C, a vacuuming time of 20 seconds, a pressure of 0.4 MPa, and a pressurizing time of 40 seconds. Using a parallel light exposure machine (manufactured by EXP2960 ORC Co., Ltd.), Kodak step tablet No. 2 was placed on it and solid exposure was performed at the optimal exposure amount such that the number of steps after development was 5 steps. After peeling off the polyethylene film, development was carried out for 30 seconds using a 1% Na2CO3 aqueous solution at 30°C under the condition of a spray pressure of 0.1 MPa. Then, it was heated at 130°C for 60 minutes in a hot air circulation drying oven for thermosetting to obtain a substrate for COP adhesion evaluation with a cured film thickness of 8 μm. For each evaluation substrate obtained above, in accordance with JIS K5400, 100 grids (10×10) of 1 mm 2 were made on the cured film on the substrate, and a transparent adhesive tape (manufactured by Nichiban Co., Ltd., width: 18 mm) was completely adhered onto all the grids. Immediately, while keeping one end of the tape perpendicular to the COP film, it was instantaneously pulled off, and observed with an optical microscope (VHX-7000, manufactured by Keyence Corporation) at a magnification of 500 times, and the number of grids that remained without being completely peeled off was examined. The adhesion of the cured film was evaluated according to the following criteria, and the evaluation results are shown in Table 1. A+: 100% of the grids remained A: 95% or more and less than 100% of the grids remained B: 90% or more and less than 95% of the grids remained C: Less than 90% of the grids remained

[0090] <Adhesion on Cu> The biaxially stretched polypropylene film of the dry film prepared in <Preparation of dry film for evaluation> was peeled off, and the exposed resin layer side was attached so that it was in contact with a copper-clad laminate with a thickness of 1.8 mm, which had been oxide-removed with a 5% sulfuric acid aqueous solution, and the copper-clad laminate and the dry film were laminated using a two-chamber vacuum laminator (Nikko Materials Co., Ltd., CVP-300) under conditions of temperature 70°C, vacuum time 20 seconds, pressure 0.4 MPa, and pressure time 40 seconds, using only the first chamber, and a parallel light exposure machine (EXP2960, ORC Seisakusho Co., Ltd.) was used to place Kodak step tablet No. 2 on the dry film and expose it to light at the optimal exposure amount so that the number of steps after development would be 5. After peeling off the polyethylene film, the film was developed for 30 seconds using a 1% Na2CO3 aqueous solution at 30°C under conditions of a spray pressure of 0.1 MPa. Thereafter, the coating was cured by heating at 130° C. for 60 minutes in a hot air circulation drying oven, to obtain a substrate for evaluating adhesion on Cu on which a fully cured product having a film thickness of 8 μm was formed. For each evaluation substrate obtained, in accordance with JIS K5400, a 1 mm 2 A total of 100 grids (10 x 10) were made, and transparent adhesive tape (manufactured by Nichiban Co., Ltd., width: 18 mm) was completely attached to all of the grids. One end of the tape was immediately pulled away instantly while being held perpendicular to the copper-clad laminate, and the number of grids that remained without being completely peeled off was counted by observing at a measurement magnification of 500 times using an optical microscope (Keyence Corp., VHX-7000). The adhesion of the cured product was evaluated according to the following criteria, and the evaluation results are shown in Table 1. A+: 100% of the lattice remains A: 95% or more but less than 100% of the lattice remains B: 90% or more but less than 95% of the lattice remains C: Less than 90% of the lattice remains

[0091] [Table 1] [Industrial Applicability]

[0092] The transparent resin composition of the present invention is excellent in transparency, developability and adhesion, and therefore can be used for forming a protective film for transparent electronic parts.

Claims

1. An alkali-soluble polymer (A) containing a cyclohexyl group and a carboxyl group and having an ethylenically unsaturated group; a carboxyl group-containing urethane resin (B) obtained by using a compound having an isocyanate group that is not directly bonded to an aromatic ring; A polymerizable compound (C) having an ethylene oxide skeleton and an unsaturated double bond; Including, the content of the alkali-soluble polymer (A) is 45 to 75 parts by mass in terms of solid content, relative to 100 parts by mass of the total of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B); a transparent resin composition in which the content of the polymerizable compound (C) is 20 parts by mass or more, calculated as a solid content, when the total amount of the alkali-soluble polymer (A) and the carboxyl group-containing urethane resin (B) is 100 parts by mass.

2. The transparent resin composition according to claim 1 , further comprising a polymerization initiator.

3. The transparent resin composition according to claim 1 or 2, which comprises an epoxy resin.

4. A dry film obtained by applying the transparent resin composition according to claim 1 to a first film.

5. A cured product obtained by using the transparent resin composition according to claim 1 or the dry film according to claim 4.

6. The cured product according to claim 5, which has a transmittance of 85% or more as measured under the following conditions: (conditions) The transparent resin composition is applied onto the first film so that the film thickness after drying is 8 μm, and then heated and dried in a hot air dryer at 80° C. for 30 minutes to form a resin layer. A COP having a thickness of 50 μm is attached to the exposed surface of the resin layer to perform lamination. After solid exposure using a parallel light exposure machine, the first film was peeled off and the plate was exposed to 1% Na 2 CO 3 Development is carried out for 30 seconds using an aqueous solution at a spray pressure of 0.1 MPa. Thereafter, the coating is thermally cured by heating in a hot air circulation drying oven at 130° C. for 60 minutes to obtain a substrate for transmittance measurement having a cured product having a film thickness of 8 μm. The transmittance of the resulting cured product in the range of 380 to 780 nm is measured using an ultraviolet-visible spectrophotometer.

7. An electronic part comprising the cured product according to claim 5 which is used as an insulating protective film for a transparent electronic part.

Citation Information

Patent Citations

  • Photocurable resin composition, dry film, cured article, and printed wiring board

    JP2011164270A

  • Flame retardant thermosetting resin composition, cured product of the same, and printed wiring board using the same

    JP2012219232A

  • Polyurethane resin, method for producing polyurethane resin and resin composition

    JP2016089172A

  • Curable resin composition, dry film, cured product and electronic component

    JP2021138916A

  • Thermosetting composition and cured product

    JP2022018893A